Publicação digital : a presença dos novos media na ilustração - Carvalho, Teresa Silva, 1991- (2018)
This paper covered the subject of illustration applied to digital publications. The recent development of different electronic devises able to read documents opened the doors to different types of publications containing different types of media. The illustration viewed in digital devices now has the possibility of containing media that changes its relation with the observer. It was the intent of this dissertation to understand what is being made in this new area of illustration, how does this type of image works, and what are the differences in the process of drawing when creating an illustration for this format. To this end, both a theoretical and practical research was conducted on the matter. On the theoretic part, the examination focused on the conditions that allowed the development of digital publications with characteristics specific to the reading device, on the nature of these characteristics, and how they work. For this purpose artists, illustrations and publications that made use of this new format were referenced as examples. Within the media contained in digital format publications particular attention was paid to animation and interaction for these have greater influence on the image and are more relevant when it comes to drawing. As for the practical portion, a selected book was illustrated for the purpose of case study. It was intended to practice the several techniques and properties studied in the theory part of the dissertation and also to better understand the process of drawing an illustration with animation or interactive elements. The end result was an illustrated digital album. In a report written to finalize the theoretical assignment, the several steps of the process were described, as well as the decisions, difficulties and breakthroughs that occurred during the process. This information complements the theory in a way that allows a better understanding of the workings of this type of illustration and the relevance of the digital format as a final format in the process of drawing